2012
DOI: 10.1002/aenm.201100446
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Doping, O2‐Stable, n‐Type Interfacial Layer for Organic Electronics

Abstract: Solid fi lms of a water-soluble dicationic perylene diimide salt, perylene bis(2ethyltrimethylammonium hydroxide imide), Petma + OH − , are strongly doped n-type by dehydration and reversibly de-doped by hydration. The hydrated fi lms consist almost entirely of the neutral perylene diimide, PDI, while the dehydrated fi lms contain ∼ 50% PDI anions. The conductivity increases by fi ve orders of magnitude upon dehydration, probably limited by fi lm roughness, while the work function decreases by 0.74 V, consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 43 publications
(42 reference statements)
3
83
0
Order By: Relevance
“…86 Efficient n-type doping has been achieved by the addition of pendant trimethyl amine groups to molecular perylene-diimide derivatives, 81 Gregg et al reported a reversible self-doping mechanism of a water soluble PDI derivative through low temperature treatment and conductivities up to 10 −3 S.cm −1 achieved. 84 Segalman and co-workers recently presented that self-doped PDIs have one of the highest n -type thermoelectric performance of solution-processed organic materials reported so far. 82 They reported PDI derivatives with various chain lengths that are strongly correlated to the morphology and electronic properties.…”
Section: N-type Organic Thermoelectric Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Efficient n-type doping has been achieved by the addition of pendant trimethyl amine groups to molecular perylene-diimide derivatives, 81 Gregg et al reported a reversible self-doping mechanism of a water soluble PDI derivative through low temperature treatment and conductivities up to 10 −3 S.cm −1 achieved. 84 Segalman and co-workers recently presented that self-doped PDIs have one of the highest n -type thermoelectric performance of solution-processed organic materials reported so far. 82 They reported PDI derivatives with various chain lengths that are strongly correlated to the morphology and electronic properties.…”
Section: N-type Organic Thermoelectric Materialsmentioning
confidence: 99%
“…Chabinyc and Segalman and others recently demonstrated the introduction of extrinsic dopants that localizes the dopants within the active host matrix and create high electrical conductivity and thermoelectric performance. [81][82][83][84] Recently, perlyenediimides (PDIs) emerged as solution processable organic semiconductors that have high EA (∼4.0 eV) where the structural modifications enable to tune the energetic levels. 85 Chemical modifications of the PDI core can deliver water soluble derivatives enabling a pathway toward non-toxic, solution processing of thin films.…”
Section: N-type Organic Thermoelectric Materialsmentioning
confidence: 99%
“…Compared to other cathode interfacial layer materials, advantages of alcohol/water-soluble organic materials are apparent in the PSCs due to their simple, vacuum-free and environment-friendly procedure to form film during the device fabrication and universality for different active layer and different metal cathode [22,23]. So far reported CILs improving the device performance mainly consist of polymers [24][25][26][27][28][29][30][31][32][33][34] and organic small molecules [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Compared to polymers, organic small molecules are more attractive because of their several intrinsic advantages over the conjugated polymer counterpart in terms of easy purification, monodispersity and well-defined structures without end group contaminants and better batch-to-batch reproducibility.…”
Section: Introductionmentioning
confidence: 98%
“…Compared to polymers, organic small molecules are more attractive because of their several intrinsic advantages over the conjugated polymer counterpart in terms of easy purification, monodispersity and well-defined structures without end group contaminants and better batch-to-batch reproducibility. Successful alcohol/water soluble small molecular CIL materials include fullerene derivatives [35][36][37][38][39], perylene diimides [40,41], porphyrin [42], pyridinium salt [43], rhodamine with inner salt [44], quinacridone tethered with sodium sulfonate [45], triphenylamine-uorene core featuring a phosphonate side chain [46], tetra-n-alkyl ammonium bromides [47], and metallophthalocyanine (MPc) derivative [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the potential to change their structural features simply by: varying the nature of the cation and/or the anion; tuning them by introducing small structural changes in the constituting ions, or of the spacers separating them provides the opportunity to obtain materials with sets of desired properties suitable for different applications. They have been applied as a chemical anchorage on a solid support [10], starting materials for the synthesis of molecular devices [11,12], reaction media or catalysts, immobilization of catalysts [9], reaction media for high-temperature organic reactions [13,14], catalysts [15], receptors for anion recognition [16], low-molecular-weight gelators [17], fluorescent organic salts [18,19], energetic materials [20,21], for use in the preparation of solid films for organic electronic applications [22] and electrowetting materials [23]. Heteromolecules including imidazole, 1,10-phenanthroline, pyridine and others have been used as the starting materials for the synthesis of polycationic organic salts.…”
Section: Introductionmentioning
confidence: 99%